2016
DOI: 10.1111/pde.12849
|View full text |Cite
|
Sign up to set email alerts
|

Alopecia Areata After Vaccination: Recurrence with Rechallenge

Abstract: Alopecia areata (AA) is the most common form of hair loss in children. We report the case of a child who had two episodes of AA after two different vaccines with complete hair regrowth between the episodes. This case supports the concept that vaccination might be a trigger for the development of AA in genetically predisposed children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 6 publications
1
29
0
Order By: Relevance
“…Others include vaccinations, febrile illness, and drugs. A low frequency of alopecia areata was reported to arise shortly after vaccinations against a variety of human pathogens including Japanese encephalitis 96 , hepatitis B virus 97 , Clostridium tetani 98 , herpes zoster virus 99 , and papillomavirus 100 . By contrast, one report showed that alopecia areata was triggered or exacerbated by swine flu virus infection 101 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…Others include vaccinations, febrile illness, and drugs. A low frequency of alopecia areata was reported to arise shortly after vaccinations against a variety of human pathogens including Japanese encephalitis 96 , hepatitis B virus 97 , Clostridium tetani 98 , herpes zoster virus 99 , and papillomavirus 100 . By contrast, one report showed that alopecia areata was triggered or exacerbated by swine flu virus infection 101 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…Low incidence of alopecia areata has also been observed shortly after vaccinations against a variety of human pathogens including, hepatitis B virus [108], Clostridium tetani [109], herpes zoster virus [110], Japanese encephalitis [111] and human papillomavirus [112]. The disease in these cases may be a result of a hypersensitive reaction to vaccines in patients that are genetically predisposed.…”
Section: Infectious Agents Are Linked To Onset and Progression Of Alomentioning
confidence: 99%
“…AA is one of the most common autoimmune diseases, with a lifetime incidence of 2·1% and prevalence of 0·1–0·2% . AA develops in genetically predisposed individuals, usually with no identifiable trigger factor, although viral infection, vaccination and psychological stress have been reported in association with disease onset . Hair loss caused by AA is sometimes considered solely a cosmetic problem, despite being associated with significant psychological distress and increased risk of developing inflammatory comorbidities .…”
mentioning
confidence: 99%
“…1,2 AA develops in genetically predisposed individuals, usually with no identifiable trigger factor, although viral infection, vaccination and psychological stress have been reported in association with disease onset. [3][4][5] Hair loss caused by AA is sometimes considered solely a cosmetic problem, despite being associated with significant psychological distress 6 and increased risk of developing inflammatory comorbidities. 7 Treatment options for AA include contact sensitizers or topical, intralesional or systemic steroids, but their efficacy is limited and treatment is commonly ineffective for extensive AA.…”
mentioning
confidence: 99%